(3cJGH aj CfhGY GdJhMjOs ((3eMeO Hf YHOGdQDa s)
(3ChdgG (B:s
(3afbhd GdJhMjO fhYGf JhMjO GdHhHjI hgh Gf Gddg SHNGfg oefaQO HGdNdb IGJOHjQ s
(3BNQgG (B:s
(3jH YdjfG EJHGYge Ud Gddg Ydi SjOfG eMeO hBdg hCUMGHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B14/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(D 404) s
Keywords: (3GdJhMjO hGdedd hGdfMds